Feature-based interaction between masks and target in continuous flash suppression - Jan Drewes; Christoph Witzel; Weina Zhu (Scientific Reports, 2023)
Abstract Continuous flash suppression (CFS) has become one of the most popular tools in the study of visual processing in the absence of conscious awareness. Studies use different kinds of masks, like colorful Mondrians or random noise. Even though the use of CFS is widespread, little is known about some of the underlying neuronal mechanisms, such as the interactions between masks and stimuli. We designed a b-CFS experiment with feature-reduced targets and masks in order to investigate possible effects of feature-similarity or -orthogonality between masks and targets. Masks were pink noise patterns filtered with an orientation band pass to generate a strong directionality. Target stimuli were Gabors varying systematically in their orientational alignment with the masks. We found that stimuli whose orientational alignment was more similar to that of the masks are suppressed significantly longer. This feature-similarity (here: orientation) based enhancement of suppression duration can be overcome by feature orthogonality in another feature dimension (here: color). We conclude that mask–target interactions exist in continuous flash suppression, and the human visual system can use orthogonality within a feature dimension or across feature dimensions to facilitate the breaking of the CFS.